Vitiligo, alkaptonuria, and nitisinone—A report of three families and review of the literature. Issue 1 (14th June 2021) - Ranganath, Lakshminarayan; Khedr, Milad; Evans, Leanne A.; Bygott, Helen; Luangrath, Emily; West, Elizabeth
Abstract: Four patients, from three families, with alkaptonuria receiving 4‐hydroxyphenylpyruvate dioxygenase‐inhibiting nitisinone therapy, which lowers homogentisic acid and increases tyrosine, developed vitiligo. Three of the four patients were receiving nitisinone 2 mg daily, while the fourth was on 10 mg daily. All four patients were either receiving or had received transiently proton‐pump inhibitors as therapy for dyspepsia. The ages of the patients were 35, 42, 40, and 67 years, respectively. Three patients were men and one was a woman. All four patients were either taking a proton‐pump inhibitor or had been taking one at some point. Three of the four were of South Asian and one of Caucasian background. The three patients with South Asian background also had either a personal or family history of autoimmune disease. Distressing vitiligo, initially in an acrofacial distribution, developed unexpectedly in these four patients, before then progressing to involve other parts of the body. Potential factors in the appearance of vitiligo in this setting, including nitisinone and other drug therapy, are explored and responses to the appearance of vitiligo are discussed.